Opportunities of HDP - Nexus in Tackling Recurring Environmental Conflicts in Somalia - Abdifatah Osman, Hussein (International Journal of Conflict Management, 2023)
Purpose: The primary goals of this paper was to identify Opportunities HDP - nexus in tackling recurring environmental conflicts in Somalia Methodology: A five-step thematic methodology was used to transcribe qualitative data from the non-structured probing question added by the researcher wanting more views on familiarity and Experience of HDP among the interviewees. The five-step included data Familiarizing, generating initial code, defining and collating interpretive code for entire data framed into themes, and defining and naming pieces.The Sample size was 112 humanitarian stakeholders, non-staff and staff personnel operating in Somalia. Results: Results showed gendered differences; 64.5% of males (40) and female participants (22)35.5% responded to the interviews implying that males dominated humanitarian operations. The Mean Age of respondents was 37.15 years, while the minimum and maximum ages were 24 and 61, respectively. Overall, HDP nexus can be concluded in playing a massive role in shaping HDP opportunities (humanitarian, funding, and programs) due to theinter link of HDP inputs, outputs, and outcomes involved. Unique Contribution to Theory, Policy and Practice:.Consequently, this paper recommends HDP - nexus Opportunities efforts approach in tackling recurring environmental conflicts in Somalia.